Protective Effects Of Apocynin And Catalase In Oxidative Stress Of Renal Failure, Hypertension And Hypotension Rat Models - Tan, Yong Chia (2020)
Oxidative stress is involved in the pathogenesis of several renal and cardiovascular diseases. In many of these diseases, there is an enhanced expression of nicotinamide adenine dinucleotide oxidase (NADPH oxidase or Nox) leading to the production of superoxide anion (O2-) and accumulation of hydrogen peroxide (H2O2) during disease progression. This study investigated the effects of apocynin, an NADPH oxidase inhibitor, and catalase, an H2O2 scavenger, on impaired renal function and haemodynamic in cyclosporine A (CsA), L-NAME and L-arginine Wistar-Kyoto rat models. Rats received CsA (25 mg/kg/day p.o.), L-NAME (15 mg/kg/day p.o.) and L- arginine (12.5 mg/ml p.o.) respectively and were assigned to the vehicle, apocynin (2.5 mmol/L p.o.), catalase (10,000 U/kg/day i.p.) or a combination of apocynin and catalase for 14 days. Renal function and haemodynamic, and plasma oxidative stress markers were measured. In addition, histological study and molecular expression of NADPH oxidase 4 (Nox 4) mRNA were assessed at the end of the treatment period.